Decline machines and economic development: rust belt cities and Flint, Michigan. Issue 2 (7th February 2022) - Wilson, David; Heil, Melissa
ABSTRACT: We develop the concept of decline machines, only recently invoked by urbanists, to understand city economic development in America's urban rust belt. We chronicle this notion and show that it currently spearheads economic development in one of America's paradigmatic rust belt cities, Flint, Michigan. We highlight, first, that Flint's machine actors creatively use imaginaries of decline to propel economic development; and second, that race is one core dimension through which this process proceeds. Coalition actors use dominant understandings of poor blackness and Latinoness – as people both primitivist exotic and frightening – to help drive economic development. The underpinning: Â austerity and neoliberal days impose profound constraints on key coalition actors, notably local planners, and local government, to create wider-ranging hunts for political resources like decline. Using this decline, economic development in Flint is shown to be more complicated in its staging, implementing, and outcomes than previously believed.